Model kepimpinan maya dan kesejahteraan kerja pemimpin sekolah malaysia: Perantaraan oleh komunikasi dalam - Mohd Yusri, Ibrahim; Wan Ismail, Wan Abdullah (2015)
Leader of modern school organization faces more frequently due to the dynamics of the workplace and situation, make them difficult to practice face to face leadership style. The study was conducted to develop a computer model of virtual leadership, intra-team communication and well-being among school leaders in Malaysia. Data of 1082 respondents were collected through the online survey and were analysed by structural equation model (SEM). The finding shown that the virtual leadership using mobile technology is significantly contributed to intra-team communication (CR=7.907, β=0.410, P=0.00), while the intra-team communication was also positively predicted towards well-being (CR=9.652, β=0.363, P=0.00). The finding also shown that the intra-team communication had fully-mediated to the relationship between virtual leadership and well-being, where the model with intra-team communication as mediator was fit better (χ2=470.206, χ2/df=4.847) than the model without mediator (χ2=656.653, χ2/df=6.633). Finally, this study has successfully developed a virtual model of leadership that can be practice by school leaders in parallel with the rapidly development of mobile technology.